Ligas do sistema Ni-Nb processadas por moagem de alta energia - Pedrosa, Marcus Túlio Magalhães Andrade (2007)
The present investigation, aim studying the Boron effect as amorphizing agent, in the Nickel-Niobium alloy, using the technique of High Energy Milling to using as master alloy for preparation of alloys Cu-Al-Ni susceptible to the shape memory effect. Using the milling of high energy is possible to extend the solubility limit of some alloy elements in the matrix. In materials whose components present remarkable gap differential in their fusing points, the master alloy can be used, with satisfactory results. For this work two milling series were accomplished, one for NiNb alloy and other series for the NiNbB alloy, with the same times of milling (1, 5, 10, 20 and 40 h). After the milling stages they were made rehearsals of x-ray diffraction, to identify the formed phases in the powders and his evolution with the milling times and thermal analysis to identify the temperatures of transformation of the present phases. System NiNb alloy with concentrations of Nb around 24% (in weight) they are easily amorphizing, being enough times of milling of 40 h. The B addition tends to accelerate the process of dissolution of Nb into Ni increasing the amorphization kinetics. The diffraction analyses XRD patterns collected in several temperatures for the amorphous powders made possible to investigate with more accuracy the B influence. When this element is added to the binary Ni-Nb alloy, the recrystallization temperatures, which they are associated to the formation of the equilibrium phase Ni3Nb, are reduced. The XRD patterns indicate also that this phase begins her formation in lower temperatures, when B is added. Therefore, was concluded that B accelerates the decomposition of the amorphous phase because of the high intensity of defects introduced during the milling process.